Wives and wanderers in a New Guinea highlands society : women's lives in the Wahgi Valley - Reay, Marie, 1922-2004 (ANU Press, 2014)
Wives and Wanderers in a New Guinea Highlands Society brings to the reader anthropologist Marie Reay's field research from the 1950s and 1960s on women's lives in the Wahgi Valley, Central Highlands of Papua New Guinea. ... Each chapter adds to the main story that Reay wanted to tell, contrasting young girls' freedom to court and choose partners, with the constraints (and violence) they were to experience as maried women."--Back cover.